2019
DOI: 10.1038/s41396-019-0392-1
|View full text |Cite
|
Sign up to set email alerts
|

Modelling microbiome recovery after antibiotics using a stability landscape framework

Abstract: Treatment with antibiotics is one of the most extreme perturbations to the human microbiome. Even standard courses of antibiotics dramatically reduce the microbiome’s diversity and can cause transitions to dysbiotic states. Conceptually, this is often described as a ‘stability landscape’: the microbiome sits in a landscape with multiple stable equilibria, and sufficiently strong perturbations can shift the microbiome from its normal equilibrium to another state. However, this picture is only qualitative and ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 51 publications
5
79
0
Order By: Relevance
“…Finally, a hallmark of the healthy adult microbial community is a stable microbial strain population as described by Shaw et al as a stability landscape (40). However, the results of our analysis using both data sets highlight that microbial strain change is inherent in developing the infant gut microbial ecosystem.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Finally, a hallmark of the healthy adult microbial community is a stable microbial strain population as described by Shaw et al as a stability landscape (40). However, the results of our analysis using both data sets highlight that microbial strain change is inherent in developing the infant gut microbial ecosystem.…”
Section: Discussionmentioning
confidence: 64%
“…Numerous studies have shown that antibiotics cause a disruption of the gut microbial composition with a long-term impact on the community structure (37)(38)(39). In a recent study, we have used our WSS strain tracking analysis to show that antibiotics can also impact the gut microbial strain stability in adults that we correlated with alterations in the "stability landscape" profile of the microbial community (28,40). In the current study, we found that the strain tracking analysis of the Yassour et al data set revealed that antibiotics had resulted in a unique strain change pattern for certain infants (19).…”
Section: Discussionmentioning
confidence: 99%
“…For the case of AMR evolution, our result that intermediate dosage therapy is optimal is particularly interesting as it may also reduce detrimental off-target species effects, such as enriching for resistance in off-target species [12] or compromising community resilience and functioning [34]. Such effects are prevalent in bacterial communities and possibly important to the AMR problem as a whole [12].…”
Section: Discussionmentioning
confidence: 99%
“…Of the remaining dynamic studies, most are not GEM-based, but rather Bayes [47,48], Lotka-Volterra [49] or Machine Learning approaches [50]. Shaw et al [47] models microbiomes experiencing perturbations, but considers only 2 states ('healthy' vs an alternative stable state). This contrasts with the MDPbiomeGEM system which can model >= 2 states undergoing perturbations.…”
Section: Comparison With Peer Approachesmentioning
confidence: 99%